Rancangan Modul Digital Hukum Islam Berbasis Kebhinnekaan di Perguruan Tinggi - Effendi, Heri; Muslim, Muslim; Pebriyenni, Pebriyenni; Aisyah, Siti (Jurusan Ilmu Sosial Politik Fakultas Ilmu Sosial Universitas Negeri Padang, 2023)
This journal article delves into the creation of a digital module for Islamic law, with a focus on promoting diversity in higher education. The study aims to contribute to the ongoing discourse on effective teaching methodologies in response to the challenges posed by the digital age. The research employs a qualitative approach, specifically library research, involving data interviews, observations, and documentation. The findings highlight essential aspects related to digital modules in higher education, emphasizing the incorporation of diversity. These aspects include the inclusion of various inspiring stories, structured group activities, and the ability to encourage reflective learning. As facilitators of learning, educators must design digital teaching materials that align with contemporary student characteristics and address pertinent issues, fostering adaptive and tolerant attitudes towards transformative communal problems among students.